Zoonotic pathogens in wildlife traded in markets for human consumption, Laos - Nawtaisong, P; Robinson, MT; Khammavong, K; Milavong, P; Rachlin, A; Dittrich, S; Dubot-Pérès, A; Vongsouvath, M; Horwood, PF; Dussart, P; Theppangna, W; Douangngeum, B; et al. (Centers for Disease Control and Prevention, 2022)
We tested animals from wildlife trade sites in Laos for the presence of zoonotic pathogens. Leptospira spp. were the most frequently detected infectious agents, found in 20.1% of animals. Rickettsia typhi and R. felis were also detected. These findings suggest a substantial risk for exposure through handling and consumption of wild animal meat.